2014
DOI: 10.29047/01225383.32
|View full text |Cite
|
Sign up to set email alerts
|

Review of studies on asphaltene - wax interaction and the effect thereof on crystalilization

Abstract: T his paper reviews the impact of asphaltenes on wax crystallization and on the properties of crude oils, and the consequences thereof on the flow assurance of waxy crude oil. It initially includes studies of the crystallization of both pure n-alkanes as well as the mixtures thereof, because they have led to an understanding of how their precipitation occurs along with their transitions of crystalline phases, particularly, by studies of X-ray diffraction (XRD). This is followed by the studies and results of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…A current description establishes that the chemical structure of asphaltenes is generally composed of polyaromatic cores attached to aliphatic chains, and they contain metals, such as vanadium, iron, and nickel, and heteroatoms, such as nitrogen, oxygen, and sulfur (Mullins, 2010). These heteroatoms polar functional groups are primarily responsible for the high dipole moment of asphaltenes promoting asphaltene self-association (Ariza-León, Molina-Velasco, Chaves-Guerrero, 2014;Goual and Firoozabadi, 2002). Asphaltene content in the oil depends on their classification, which is based on the American Petroleum Institute (API) gravity.…”
Section: Introductionmentioning
confidence: 99%
“…A current description establishes that the chemical structure of asphaltenes is generally composed of polyaromatic cores attached to aliphatic chains, and they contain metals, such as vanadium, iron, and nickel, and heteroatoms, such as nitrogen, oxygen, and sulfur (Mullins, 2010). These heteroatoms polar functional groups are primarily responsible for the high dipole moment of asphaltenes promoting asphaltene self-association (Ariza-León, Molina-Velasco, Chaves-Guerrero, 2014;Goual and Firoozabadi, 2002). Asphaltene content in the oil depends on their classification, which is based on the American Petroleum Institute (API) gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatoms, such as oxygen, nitrogen, sulfur or certain metals, are found in asphaltenes as well. The effect of asphaltenes on wax precipitation is discussed contradictorily in literature [16]. It has been reported that the presence of asphaltenes decreases pour point and strength of the formed wax-oil gel [26][27][28][29].…”
Section: Introductionmentioning
confidence: 96%
“…In addition to asphaltene adsorption, there is at least one another highly competitive mechanism responsible for severe formation damage and to pipeline transportation problems, that is, paraffin wax deposition. Though the primary cause of wax deposition is a loss in solubility in the crude oil, some reports suggest that asphaltenes play an important role providing crystal nucleation sites or simply restricting the diffusion of paraffins (the opposite effect on diffusion was also regularly reported). , A good review on the topic of asphaltene effects on wax crystallization is provided by Ariza-Léon et al So far, there is no consensus regarding the direction and magnitude of the effect of asphaltenes on wax precipitation, point of crystallization, pour point, and rheology of a host fluid.…”
Section: Introductionmentioning
confidence: 99%